Cognitive Impairment after Mild Stroke: Development and Validation of the SIGNAL2 Risk Score. - Kandiah, Nagaendran; Chander, Russell Jude; Lin, Xuling; Ng, Aloysius; Poh, Yen Yeong; Cheong, Chin Yee; Cenina, Alvin Rae; Assam, Pryseley Nkouibert (J Alzheimers Dis, 2016)
BACKGROUND: Post stroke cognitive impairment (PSCI), an important complication of strokes, has numerous risk factors. A scale adequately classifying risk of cognitive impairment 3-6 months after mild stroke will be useful for clinicians. OBJECTIVE: To develop a risk score based on clinical and neuroimaging variables that will be useful in identifying mild ischemic stroke patients at high risk for PSCI. METHODS: The risk score development cohort comprised of a retrospective dataset of 209 mild stroke patients with MRI confirmed infarcts, without pre-stroke cognitive impairment, and evaluated within 6 months post-stroke for PSCI. Logistic regression identified factors predictive of PSCI and a risk score was developed based on regression coefficients. The risk score was checked for stability using 10-fold cross-validation and validated in an independent prospective cohort of 185 ischemic mild stroke patients. RESULTS: Within 6 months post-stroke, 37.32% developed PSCI in the retrospective dataset. A 15-point risk score based on age, education, acute cortical infarcts, white matter hyperintensity, chronic lacunes, global cortical atrophy, and intracranial large vessel stenosis was highly predictive of PSCI with an AUC of 0.829. 10.11% with low scores, 52.69% with moderate scores, and 74.07% with high scores developed PSCI. In the prospective validation cohort, the model had an AUC of 0.776, and exhibited similar accuracy and stability statistics at both 6 and 12 months. CONCLUSION: The seven item risk score adequately identified mild stroke patients who are at an increased risk of developing PSCI.
Keywords: Aged; Aging; Area Under Curve; Brain; Brain Ischemia; Cognition Disorders; Constriction, Pathologic; Educational Status; Female; Follow-Up Studies; Humans; Logistic Models; Male; Middle Aged; Prospective Studies; Retrospective Studies; Risk; Severity of Illness Index; Stroke; White Matter